Género y crítica en la prosa médica escrita en español: Función comunicativa y relación de poder - Ariza, María Ángeles Alcaraz; Salager-Meyer, Françoise (HERMES - Journal of Language and Communication in Business, 2002)
This study addresses the issue of academic conflict (AC) in four different genres of medical discourse, viz., editorials, review and research papers and case reports. The rhetorical strategies used to convey AC were recorded and their qualitative features (their level of commitment or detachment, their overall tone, the presence of irony, sarcasm, etc.) were analyzed in 40 medical articles written in Spanish in the last decade of the 20th century. Our results show that the communicative function of each genre and the rank/status power relations that exist between authors and their audience have a direct bearing on the way medical researchers express their dissension.